AGGRESSIVE REVASCULARIZATION IN PATIENTS WITH CRITICAL LOWER LIMBS ISCHEMIA - Bashir, Eitezaz Ahmed (Journal of Ayub Medical College Abbottabad, 2005)
Background: This study was conducted to conduct an audit of our policy of aggressive arterial reconstruction in patients with critical lower limb ischemia, so as to determine the success in treatment of these cases in terms of limb salvage and patient survival. Methods: This study was carried out at department of general and vascular Surgery, Combined Military Hospital Rawalpindi from January 1995 to January 2000. A total of 114 cases were studied. All patients were admitted for assessment of an ischemic leg. Pre operative angiography was routinely performed. All patients underwent definitive treatment (bypass surgery, amputation and lumber sympathectomy) within three days of admission. Pre operative risk factors including age, sex, preexisting diabetes mellitus, presenting symptoms, ankle systolic pressure were evaluated, with their effect on limb salvage and patient survival. Results: Of the 114 cases included 102 (89.5%) were males. Forty-six patients (40.3%) were diabetic. Revascularization was attempted in 76 limbs, 61 (80.3%) underwent femoropopliteal bypass and 15 (19.7%) underwent femorodistal bypass. Twenty patients (17.5%) with Berger's disease, of the 114 cases included, were treated by lumbar sympathectomy. Eighteen limbs were beyond salvage necessitating amputation. Risk factors had no effect on limb salvage or mortality. Overall mortality was 4% and over all 30-day graft patency rate was 77.7%. One-year graft patency rate was 62.5%. Conclusion: By pursuing an aggressive policy of revascularization, good results can be obtained in terms of limb salvage and survival rates. Key Words: Critical ischemia, femoropopliteal bypass, amputation, saphenous vein.